Polyhydramnios in isolated oral cleft pregnancies: incidence and outcome in a retrospective study. (24th January 2017) - Depla, Anne L.; Breugem, Corstiaan C.; van der Horst, Chantal M. A. M.; de Heus, Roel; van den Boogaard, Marie‐José H.; Maas, Saskia M.; Pajkrt, Eva; Bekker, Mireille N.
Abstract: Objectives: Polyhydramnios is suggested to be associated with oral clefts (OCs) due to swallowing problems. This study assessed incidence and outcome of idiopathic polyhydramnios in isolated OC pregnancies. Methods: This was a retrospective cohort study of prenatally diagnosed OC. The incidence of idiopathic polyhydramnios in isolated OC pregnancies was determined. Pregnancy outcome, neonatal and paediatric follow‐up were compared between cases with polyhydramnios and those with normal amniotic fluid. Subgroup analysis was conducted to evaluate whether an association exists between polyhydramnios and presence of associated anomalies diagnosed after birth. Results: In 230 cases of isolated OC, 15 developed polyhydramnios (6.5%). Involvement of the palate was significantly more common in the presence than in the absence of polyhydramnios (13/15 or 87% vs 125/215 or 58%, p = 0.03, odds ratio 4.7, 95% confidence interval 1.0–30.8). No significant differences were seen in pregnancy outcome or neonatal and paediatric follow‐up between the two groups. In subgroup analysis, rate of polyhydramnios was not significantly different in associated cases that appeared isolated prenatally (1/27; 3.7%) compared with that in the isolated cases (15/230; 6.5%). Conclusions: The incidence of idiopathic polyhydramnios in isolated OC pregnancies is 6.5%. Polyhydramnios in isolated OC increases the risk of palate involvement. The presence of polyhydramnios is not associated with adverse perinatal or long‐term outcome. If isolated at prenatal assessment, polyhydramnios does not increase the risk of associated anomalies postpartum. © 2016 John Wiley & Sons, Ltd. Abstract : WHAT's ALREADY KNOWN ABOUT THIS TOPIC? Oral clefts are amongst the most prevalent congenital malformations, and their prenatal detection has increased in the past decade through advancements in ultrasound screening and technique. Polyhydramnios is suggested to be associated with oral clefts due to swallowing problems, although this relation has not been studied in pregnancies of fetuses with an isolated oral cleft. WHAT DOES THIS STUDY ADD? The incidence of isolated polyhydramnios in isolated oral cleft pregnancies was 6.5%, against 1 to 2% in general pregnancies. Polyhydramnios appeared to be a marker for palate involvement, which is hard to assess prenatally and may indicate swallowing problems in utero. Pregnancy and neonatal outcome were not impaired in polyhydramnios cases; polyhydramnios did not increase the risk for finding associated anomalies after birth.